Association between age and knee structural change: a cross sectional MRI based study. Issue 4 (15th March 2005) - Ding, C; Cicuttini, F; Scott, F; Cooley, H; Jones, G
Abstract : Objective: To describe the associations between age, knee cartilage morphology, and bone size in adults. Methods: A cross sectional convenience sample of 372 male and female subjects (mean age 45 years, range 26–61) was studied. Knee measures included a cartilage defect five site score (0–4 respectively) and prevalence (defect score of ⩾2 at any site), cartilage volume and thickness, and bone surface area and/or volume. These were determined at the patellar, medial, and lateral tibial and femoral sites using T1 weighted fat saturation MRI. Height, weight, and radiographic osteoarthritis (ROA) were measured by standard protocols. Results: In multivariate analysis, age was significantly associated with knee cartilage defect scores (β = +0.016 to +0.073/year, all p<0.01) and prevalence (OR = 1.05–1.10/year, all p<0.05) in all compartments. Additionally, age was negatively associated with knee cartilage thickness at all sites (β = −0.013 to −0.035 mm/year, all p<0.05), and with patellar (β = −11.5 μl/year, p<0.01) but not tibial cartilage volume. Lastly, age was significantly positively associated with medial and lateral tibial surface bone area (β = +3.0 to +4.7 mm 2 /year, all p<0.05) and patellar bone volume (β = +34.4 μl/year, p<0.05). Associations between age and tibiofemoral cartilage defect score, cartilage thickness, and bone size decreased in magnitude after adjustment for ROA, suggesting these changes are directly relevant to OA. Conclusion: The most consistent knee structural changes with increasing age are increase in cartilage defect severity and prevalence, cartilage thinning, and increase in bone size with inconsistent change in cartilage volume. Longitudinal studies are needed to determine which of these changes are primary and confirm their relevance to knee OA.